Peran Tulisan Jawi dalam Pelestarian Tradisi Arab-Melayu di Nusantara - Adrian Maulana; Sri Mawaddah (Pustaka Digital Indonesia, 2025)
The urgency of this research lies in examining the role of Jawi script as a modified Arabic script used to write the Malay language, as well as its contribution to the spread of Islam and the formation of Arab-Malay cultural identity in the Nusantara. This study aims to describe the contribution of Jawi script in preserving the cultural values and traditions of the Malay community. This research employs a qualitative descriptive method. Data collection techniques include library research and digital documentation. The researcher applies source triangulation to ensure data validity. Data analysis is carried out using content analysis methods. The results show that Jawi script is not only a means of communication and Islamic propagation, but also a cultural heritage that records the intellectual and spiritual legacy of past societies. Although its usage has declined in recent times, various preservation efforts such as manuscript digitization and Jawi instruction in educational institutions are being promoted. The preservation of Jawi script is a strategic step in safeguarding the Arab-Malay cultural identity and heritage amidst the current of modernization.